2018
DOI: 10.1002/jia2.25149
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based differences in antiretroviral therapy initiation, switching and treatment interruptions: global overview from the International Epidemiologic Databases to Evaluate AIDS (IeDEA)

Abstract: IntroductionIn 2015, the World Health Organization recommended that all HIV‐infected individuals consider ART initiation as soon as possible after diagnosis. Sex differences in choice of initial ART regimen, indications for switching, time to switching and choice of second‐line regimens have not been well described. The aims of this study were to describe first‐line ART and CD4 count at ART initiation by sex, calendar year and region, and to analyse time to change or interruption in first‐line ART, according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Our finding that men and pregnant or breastfeeding women were at an increased risk of LTFU corroborates the results from other studies in sub‐Saharan Africa . For pregnant women in particular, it has been hypothesised that they are more likely to disengage from care because they are often asymptomatic and discontinue treatment once the risk of onwards transmission to her child has dissipated .…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that men and pregnant or breastfeeding women were at an increased risk of LTFU corroborates the results from other studies in sub‐Saharan Africa . For pregnant women in particular, it has been hypothesised that they are more likely to disengage from care because they are often asymptomatic and discontinue treatment once the risk of onwards transmission to her child has dissipated .…”
Section: Discussionsupporting
confidence: 91%
“… Context: Global data suggest that the timeliness of ART initiation, as measured by the level of immunodeficiency at the start of ART, is highly suboptimal in relation to WHO guidelines, particularly in SSA, where a recent analysis of data from 767,000 patients in 21 countries showed that median CD4 counts at ART initiation remained below 300 cells/mm 3 in 2015 . Infants, adolescents, and men, in particular, are more likely to initiate treatment late and to not be retained in care . Research approaches : Important factors for further study include quality of care; policy and administrative requirements; costs of services, including user fees; HIV‐related stigma; integrated screening and treatment of other health conditions (i.e. non‐communicable diseases); and community‐ and home‐based services (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…), stigma remains a barrier to HIV care, contributing to delays in ART initiation . Men, particularly, are not adequately served by traditional approaches, as they remain less likely than women to start ART and they have more advanced disease than women when they start ART . Wide‐scale implementation of Option B+ may further increase gender disparities in access to ART, as has been reported in Malawi and Mozambique .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Country-specific guidelines do not necessarily keep apace with evolving WHO guidelines and individual countries may also vary in their approach to HIV testing [14]. One prior multi-country cohort study described gender-based regional variations in ART regimen selection, changes and discontinuations and found that median CD4 count was consistently lower in West Africa as compared to East Africa [15].…”
Section: Time To Art Initiationmentioning
confidence: 99%